TIMP3 promotes the maintenance of neural stem-progenitor cells in the mouse subventricular zone - Fang, Lingyan; Kuniya, Takaaki; Harada, Yujin; Yasuda, Osamu; Maeda, Nobuyo; Suzuki, Yutaka; Kawaguchi, Daichi; Gotoh, Yukiko (Frontiers in Neuroscience, 2023)
Adult neural stem cells (NSCs) in the mouse subventricular zone (SVZ) serve as a lifelong reservoir for newborn olfactory bulb neurons. Recent studies have identified a slowly dividing subpopulation of embryonic neural stem-progenitor cells (NPCs) as the embryonic origin of adult NSCs. Yet, little is known about how these slowly dividing embryonic NPCs are maintained until adulthood while other NPCs are extinguished by the completion of brain development. The extracellular matrix (ECM) is an essential component of stem cell niches and thus a key determinant of stem cell fate. Here we investigated tissue inhibitors of metalloproteinases (TIMPs)—regulators of ECM remodeling—for their potential roles in the establishment of adult NSCs. We found that Timp2, Timp3, and Timp4 were expressed at high levels in slowly dividing NPCs compared to rapidly dividing NPCs. Deletion of TIMP3 reduced the number of adult NSCs and neuroblasts in the lateral SVZ. In addition, overexpression of TIMP3 in the embryonic NPCs suppressed neuronal differentiation and upregulated the expression levels of Notch signaling relating genes. These results thus suggest that TIMP3 keeps the undifferentiated state of embryonic NPCs, leading to the establishment and maintenance of adult NSCs.